Adaptation Strategies and Constraints To Climate Change Among Clove Farmers in East Kolaka - Khusnul Awaliyah Muliyadi; Agustina Shinta Hartati Wahyuningtyas; Sujarwo (Jurnal Manajemen dan Agribisnis, 2025)
Background: Climate change has become a major challenge for agriculture in tropical regions, particularly in East Kolaka, Southeast Sulawesi, where cloves are a vital economic crop. Gaining insight into how farmers respond to and adapt to these climatic shifts is essential for formulating effective and sustainable climate resilience policies.Purpose: This study explores the range of adaptation strategies employed by clove farmers, identifies the socioeconomic factors shaping their strategic choices, analyzes the interconnections among different adaptation measures, and evaluates the primary barriers that constrain adaptation in East Kolaka.Design/Methodology/Approach: Primary data were obtained from 138 clove farmers in Anggaloosi Village, East Kolaka Regency, Indonesia. Descriptive statistical techniques were applied to describe the adaptation strategies used. The multivariate probit model was utilized to determine the influencing factors and interrelations among the strategies, while the Constraint Facing Index (CFI) method was used to assess the dominant obstacles faced by farmers in adapting to climate change.Findings/Results: Findings revealed that 80.43% of farmers participated in training and extension programs, 73.19% utilized climate information, 71.01% implemented irrigation improvements, and 65.94% diversified their income sources. Access to extension services emerged as the most significant determinant of adaptation behavior. Several adaptation strategies were found to be complementary or substitutive. The main challenge faced by clove farmers at the research location is environmental obstacles, namely, unpredictable changes in weather patterns, with a score of 305 at a very high level of obstacles.Conclusion: The study highlights that successful adaptation among clove farmers largely relies on increased access to agricultural extension, climate-related information, and financial assistance. Originality/value (State of the art): This study adds to the scarce body of empirical evidence concerning climate change adaptation in perennial crops such as cloves in Indonesia. By combining the Multivariate Probit and Constraint Facing Index (CFI) approaches, this study provides an integrated analysis of both the determinants and barriers to adaptation, generating valuable implications for policymakers and practitioners in designing localized and inclusive climate adaptation strategies. Keywords: adaptation strategies, climate change, multivariate probit, cloves, southeast Sulawesi